Dampak Pandemi Covid-19 Terhadap Efektifitas Operasional Tol Laut Di Wilayah Indonesia Tengah - Indarno Sugeng R; Hadijah Hadijah; Buce Akhmad Syafaat; Yulinda Yusar Yusar (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
The Sea Highway is a program of the Indonesian government that aims to improve connectivity between regions, equitable distribution of goods and reduce price disparities between the western region of Indonesia and the central region of Indonesia. This program started in 2014 and is still running today. However, at the beginning of 2020, the Covid-19 pandemic hit every country including Indonesia and had an impact on all sectors, including the Sea Highway program. The purpose of the study is to determine the extent of the impact of the Covid-19 pandemic on the effectiveness of the Sea Highway, it is necessary to conduct a study to compare the operational conditions of the Sea Highway during conditions before the pandemic and during the Covid-19 pandemic. To conduct this research, it is necessary to collect primary and secondary data. The method applied in this study is a qualitative descriptive approach by collecting primary data obtained from PT Djakarta Lloyd which is directly involved in the Sea Highway program and collecting secondary data from related literature and previous research. This research is limited to Central Indonesia shipping lanes and operational effectiveness in terms of shipping route criteria. The results of this study show that the frequency of shipping, and delivery times before and during the pandemic are constant, while the number of cargoes and prices have decreased. In conclusion, this study can be the basis of a solution to increase the effectiveness of the operation of the Sea Highway during the Covid-19 pandemic.